Serum creatinine/cystatin C ratio is a systemic marker of sarcopenia in patients with gastrointestinal stromal tumours - Ding, Ping’an; Guo, Honghai; Sun, Chenyu; Chen, Shuya; Yang, Peigang; Tian, Yuan; Lowe, Scott; Zhao, Qun (Frontiers in Nutrition, 2022)
Background It is well known that sarcopenia is a common risk factor in patients with gastrointestinal tumours, which may negatively affect the clinical outcome and prognosis. Recent studies suggest that serum creatinine-cystatin C (Cr/CysC) ratio may be associated with sarcopenia, but this association lacks sufficient evidence in patients with gastrointestinal stromal tumours (GIST). Therefore, this study aimed to investigate whether the Cr/CysC ratio was associated with sarcopenia and recurrence-free survival (RFS) in patients with GIST. Materials and methods The study retrospectively analysed 413 patients with GIST who underwent surgical resection from January 2016 to January 2020. The serum Cr/CysC ratio was determined as a proxy for sarcopenia by comparing it with various biomarkers and Cox multifactorial analysis was used to determine the relationship between Cr/CysC ratio and prognosis. Results Serum Cr/CysC was positively correlated with skeletal muscle area (SMA) (r = 0.256, p < 0.001), skeletal muscle index (SMI) (r = 0.300, p < 0.001), and hand grip strength (HGS) (r = 0.251, p < 0.001). The area under the receiver operator characteristic curve for sarcopenic subjects with serum Cr/CysC ratio was significantly greater than other biomarkers (Cr/CysC: 0.840, CysC: 0.732, Cr: 0.518). The optimal cut-off value for Cr/CysC was 0.65, and patients in the high Cr/CysC group had a higher 3-year recurrence-free survival (RFS) than those in the low Cr/CysC group (92.72 vs. 72.46%, p < 0.001). Cox multifactorial analysis found that the Cr/CysC ratio was an independent risk factor for RFS in GIST patients (HR = 2.143, 95% CI: 1.431–5.459, p = 0.011). Conclusion Serum Cr/CysC ratio has satisfactory and comparable diagnostic accuracy, and prognostic value for sarcopenia in patients with GIST. Therefore, it can be a simple and practical clinical tool to screen sarcopenia in GIST patients. However, further studies are required to validate these findings.